Proximity of mandibular third molar roots with inferior alveolar canal: a radiographic study - Singh, Ashutosh Kumar; Khanal, Nikita; Dhungel, Safal (Journal of Chitwan Medical College, 2020)
Background: Mandibular third molar’s roots have close proximity to the inferior alveolar canal (IAC) and nerve. Inferior alveolar nerve injuries have been observed to occur more frequently when there is radiographic evidence of close contact of third molar roots to the IAC. Orthopantomogram is one of the commonly used diagnostic tools for evaluating the relationship between these two structures. There is lack of data regarding prevalence of these radiographic signs in Nepalese population. It was required to assess the reliability on the radiographic signs of relationship between the IAC and the third molar roots, to establish IAC as risk indicators for IAC exposure during extraction. Methods: A single centre cross-sectional descriptive study was designed where demographic data and radiographic signs of third molar roots proximity to IAC were obtained from imaging software records and descriptive analysis was performed with SPSS version 20. Results: One or more radiographic signs were observed in 49.6% of mandibular third molars. Interruption of white line followed by narrowing of canal and darkening of roots was observed in decreasing order of frequency and no statistically significant association between sex, age and side of impacted third molar with presence of radiographic signs. Conclusions: Presence of one or more radiographic signs of proximity of mandibular third molar roots with IAC in nearly half of the cases. Clinicians should be aware of risk of nerve injury on presence of these signs. Further investigation with cone beam computed tomography to rule out any nerve injury risk should be adopted into practice.